2005
DOI: 10.1080/03008200591008473
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment of Therapeutic Laser and Herbal Application Improves the Strength of Repairing Ligament

Abstract: The present study investigated the effects of combined therapeutic laser and herbal medication protocols on injured medial collateral ligaments (MCLs) of rat knees. Fully 36 rats were evenly divided into 9 groups. Right MCLs of groups 1 to 6 and 8 were transected, while that of groups 7 and 9 remained intact. After surgery, group 1 was treated with 1 session of high-dosed laser; group 2 with 9 sessions of low-dosed laser; group 3 with an herbal plaster; groups 4 and 5 received combined treatments of groups 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Preliminary findings of this study indicated that using combined MAT plus LAT exerted a relatively better effect than using MAT or LAT alone. This result agrees with the synergistic effect of combined therapeutic laser and herbal medication protocols on injured medial collateral ligaments (MCLs) of rat knees [ 24 ]. The combined protocols further enhanced the biomechanical properties of repairing rat MCLs in comparison with separate applications [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
“…Preliminary findings of this study indicated that using combined MAT plus LAT exerted a relatively better effect than using MAT or LAT alone. This result agrees with the synergistic effect of combined therapeutic laser and herbal medication protocols on injured medial collateral ligaments (MCLs) of rat knees [ 24 ]. The combined protocols further enhanced the biomechanical properties of repairing rat MCLs in comparison with separate applications [ 24 ].…”
Section: Discussionsupporting
confidence: 85%
“…LLLT is a widely studied treatment option for several different types of acute and chronic medical problems, and has been studied mostly in different types of animals until now. Some of the studies using animals as the target subjects have found some correlation between the use of LLLT and decreased healing times of wounds when compared to the control groups 6,7 . As more evidence of the statistically proven benefits of LLLT in animal trials have surfaced, some researchers have begun to shift their view to whether this treatment may have any beneficial properties in human wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 There have been a few studies regarding effects of LLLT on repairing MCL. [17][18][19] in their first study, tested the effects of a single dose of gallium-aluminum-arsenide (Ga-AlAr) laser on the strength of healing MCL in rats. Biomechanical analysis revealed ultimate tensile strength (UTS) and stiffness of laser group higher than control group.…”
Section: Introductionmentioning
confidence: 99%
“…They found UTS and stiffness of a single dose GaAlAr laser group higher than control group. 19 Fung et al suggested studying the effects of percutaneous laser therapy with multiple treatment sessions in order to simulate the normal clinical use of therapeutic laser. 19 Until now, there has been no knowledge pertaining to transmission electron microscope (TEM) study of a helium-neon laser on fibrils morphometry of repairing MCL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation